2016
DOI: 10.3390/ijms17040593
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Epidermal Growth Factor Receptors (sEGFRs) in Cancer: Biological Aspects and Clinical Relevance

Abstract: The identification of molecules that can reliably detect the presence of a tumor or predict its behavior is one of the biggest challenges of research in cancer biology. Biological fluids are intriguing mediums, containing many molecules that express the individual health status and, accordingly, may be useful in establishing the potential risk of cancer, defining differential diagnosis and prognosis, predicting the response to treatment, and monitoring the disease progression. The existence of circulating solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 70 publications
2
38
1
2
Order By: Relevance
“…Despite some reports showing increased values in affected patients, most studies (and those including a higher number of subjects) reported a decrease of serum EGFR in cancer patients, with a proportional impact on survival . This supports the hypothesis that serum EGFR could be a different isoform with a physiological and tumor‐protective role in the control of the EGFR‐regulated signaling . Similarly, we observed a reduction of serum EGFR in OSCC patients, but it was not possible to recognize any important impact on survival.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Despite some reports showing increased values in affected patients, most studies (and those including a higher number of subjects) reported a decrease of serum EGFR in cancer patients, with a proportional impact on survival . This supports the hypothesis that serum EGFR could be a different isoform with a physiological and tumor‐protective role in the control of the EGFR‐regulated signaling . Similarly, we observed a reduction of serum EGFR in OSCC patients, but it was not possible to recognize any important impact on survival.…”
Section: Discussionsupporting
confidence: 60%
“…In our experience, saliva EGFR showed higher concentrations in OSCC patients compared with healthy controls, with a further increase in more advanced tumors (pT4 category) and a consequent impact on OS. In light of this, we can hypothesize that only saliva EGFR could be the tumor‐specific soluble isoform, whereas the serum‐circulating one could have a physiological role, as suggested for non–small cell lung cancer . The discrepancy in saliva EGFR performance between the present and Bernardes et al's studies may be due to the different ELISA kits used and the different saliva collection methods that can affect the composition of the saliva samples …”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The use of serum ERBB’s as an indicator of human cancer appears useful however, its prognostic and theranostic value remains controversial and continued investigations will be required [8196, 99]. The development of a diagnostic test for preclinical DFT1 would assist in the field operations if individuals could be identified before they become infectious[110], therefore application of serum ERBB3 as a diagnostic biomarker of DFT1 has great potential.…”
Section: Discussionmentioning
confidence: 99%